OSTEOMALACIA SECONDARY TO RENAL TUBULAR ACIDOSIS TYPE 1 WITH VITAMIN D DEFICIENCY - Jeevaraj, Lavanya; Rahman, Anilah AR; Rahmatullah, Ijaz Hallaj (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Osteomalacia is a disease of inadequate bone mineralization. The true incidence of osteomalacia is largely underestimated. Patients may develop bone pain, muscle weakness and fractures and in severe untreated cases may become bedbound. Osteomalacia is known to be associated with RTA types 1 and 2. CASE We report a 41-year-old female with RTA type 1 who had presented to us after applying for disability pension. She has been having muscle weakness and bone pain which progressed to gait abnormalities and had become bedridden and dependent on activities of daily living. She previously defaulted all her follow-ups and was found to have severe vitamin D deficiency with untreated acidosis. Neuromuscular dystrophy was excluded. Her initial BMD showed a hip Z-score of -3.9 and T-score of -4.0 (April 2019). She was treated with vitamin D3 7,000 units/day (50,000 units weekly), calcium lactate 300 mg od and Shol’s solution 20 ml qid. Subsequent follow up showed gradual improvement in muscle strength with normalized BMD within 3 years and resulting in patient being independent. CONCLUSION We report the successful recognition and management of osteomalacia with RTA type 1 and Vitamin D deficiency.